Influence of Risk Management On Financial Performance of Conventional Banking (Case Study of BRI and BTN Banks) - Devi Erviana (Pustaka Digital Indonesia, 2021)
This research was conducted at Bank BRI and BTN which are listed on the Indonesia Stock Exchange for two months. Aims to determine the effect of risk management on the financial performance of conventional banking at BRI and BTN banks with quantitative research methods with a descriptive approach. The population in this study there are 2 banking companies listed on the IDX namely Bank BRI and BTN with samples namely the financial statements of Bank BRI and BTN including, statements of financial position, profit and loss position and cash flow statements. This study uses data analysis techniques ROA, CAR (Capital Asset Ratio), and BOPO (Operating Costs to Operating Income) with data collection techniques observation and study library . The results of the study indicate that the effect of risk management on conventional financial performance has an effect but only in one year between them.